German version of the specific phobia of vomiting inventory (SPOVI): psychometric properties and correlates in a clinical and non-clinical sample - Severin Hennemann; Antonia Weirich; Adrian Meule; Anne-Kathrin Bräscher; Michael Witthöft (BMC Psychiatry, 2025)
Abstract Background The Specific Phobia of Vomiting Inventory (SPOVI) is a 14-item instrument measuring behavioral avoidance and threat monitoring associated with emetophobia. The current study aimed to provide a German translation of the SPOVI and examine its psychometric properties and correlates. Methods N = 441 adults from the general population and N = 465 outpatients with mental disorders completed the SPOVI and other self-report measures. Factor structure, reliability, convergent, and discriminant validity, as well as clinical utility, were investigated. Results The German version of the SPOVI had a one-factor structure and high internal consistency in both samples (ωs > 0.90). Large correlations (rs > 0.50) with questionnaires assessing phobic anxiety, general anxiety, illness-related anxiety, and disgust sensitivity supported convergent validity, while relatively low correlations with questionnaires assessing depression, eating disorders or paranoid ideation supported discriminant validity. Among outpatients, those with a specific phobia diagnosis had the highest SPOVI scores. Conclusion The German translation of the SPOVI has sound psychometric properties and is a potentially practical clinical screening instrument for emetophobia. Pre-registration https://aspredicted.org/5y6zb.pdf .